Contrato coletivo de trabalho - Beltrame, Lucas Michelini (2010)
The normative traded instruments are an important source of formal labor law, as are the fruit of the private conference and express the conditions that were created or modified by the stakeholders themselves. These instruments are a formal collective bargaining process, where the parties must always act with transparency, good faith and loyalty. The legal traded instruments are the collective labor contract, collective bargaining agreements and collective bargaining agreement. These last two figures are well known and commonly used in labor relations. The collective agreement is a figure that has not been institutionalized in Brazil, because it was not regulated by law, nor collective entities had the organizational strength to implement it. However, it is an interesting tool that presents itself as an alternative to struggle with the current model of labor relations in our legal system. It is a tool enabling the development and maturation of the brazilian negotiating process by allowing the parties themselves to have powers to regulate their interests, reserving to the State's role as regulator, curbing abuses and excesses